Newly Diagnosed Type 1 Diabetes Mellitus: A Resident Simulation - Diane Donegan; Rose Mader; Sara Weigel; Kurt A. Kennel (Association of American Medical Colleges, 2013)
Abstract Introduction This is a five-day immersive simulation of life as a patient with newly diagnosed type 1 diabetes intended for physician trainees. The aim of the simulation was to identify physical and psychosocial barriers to diabetes management to which trainees can relate following completion of the simulation. It also sought to engage patients and collaborate with allied-health providers empowering patients to make lifestyle changes and improve disease self-management skills through a new appreciation of patient experience. Methods Following an education session with a diabetes nurse educator and dietician, residents were instructed to perform self-blood glucose monitoring four times a day; self-administer 0.9% saline in lieu of insulin, and modify and record their diet and physical activity for 3 days. Residents participating were requested to post a blog entry reflecting on their experience in preparation for a facilitated group debriefing session. Results To date over 250 residents have completed the simulation project in our establishment which began in June 2007. The concept of the blog started in April 2008. Contributions have resulted in 62 blog entries. Qualitative assessment of the entries indicated that all of those who partook in the simulation noted some element of performance challenge. Thirty entries noted difficulty with food planning and carb counting, 20 revealed fear/dread or pain with finger-prick testing, and 13 documented frustration or noncompliance. Psychosocial stressors were also appreciated with 17 entries indicating embarrassment with diabetic tasks and 19 noting conflicts with daily routine. Resident also acknowledged positive outcomes including increased empathy and improved communication skills. Twelve entries also commented specifically on the valuable resources and crucial role the certified diabetes educator and dietician. Discussion We feel that the simulation provides a better understanding of patient conflicts and despite performance challenges, was well received as part of the diabetes curriculum, and improved physician trainee attitudes.